Mapas de guia de rota em automóvel para motoristas com deficiência na visão de cores - Oliveira, Renan Furlan de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In-Car Route Guidance and Navigation System (RGNS) have been designed to people with normal color vision. However, cartographic representations of these systems can be illegible for drivers with deficiency in color vision, commonly known as color blindness. Therefore, to understand certain information in maps of RGNS can be a complex task for this group of users. This work evaluates the subjective preference of a group of drivers with color vision deficiency by using cartographic representations of RGNS, which was designed for people with this kind of perceptual characteristic. In a preliminary step it was selected a color vision simulator that best represents the color vision of color blindness, the Color Oracle. Then a graphical design analysis of two route guidance systems indicated readability and noise characteristics. Subsequently, a set of maps was designed based on aspects of color perception of individuals with color vision deficiency, and principles of cartographic communication as well. The results of the design consisted of a single representation for a background and two colors to symbolize car, direction arrow maneuver and route, totaling eight different maps. The evaluation for the preference was carried out with a group of 14 drivers with color vision deficiency. Participants' opinions suggest legibility for all representations. Although there have been no significant differences in terms of preference for different representations, the results showed that there was a trend to prefer car and the maneuver arrow outline in blue and the route in black. According to comments, this representation allowed better differentiation, identification and interpretation of the thematic cartographic symbols, both in relation to figure and background. It is recommended to evaluate the usability of these cartographic representations considering efficiency and effectiveness...

Os mapas de Sistema de Navegação e Guia de Rota em automóvel (SINGRA) têm sido projetados para atender pessoas com visão normal de cores. No entanto, as representações cartográficas apresentadas por estes sistemas podem ser ilegíveis para os motoristas com deficiência na visão de visão, popularmente conhecidos como daltônicos. Sendo assim, compreender determinadas informações nos mapas de SINGRA pode ser uma tarefa bastante complexa por parte deste grupo de usuários. Este trabalho avalia a preferência subjetiva de um grupo de motoristas daltônicos por representações cartográficas de sistemas de guia de rota em automóvel, projetadas para pessoas com esta característica perceptiva no verde e no vermelho. Uma etapa preliminar selecionou um simulador de visão de cores que melhor representa a visão de cores dos daltônicos, o Color Oracle. Em seguida, uma análise do projeto gráfico de dois sistemas de guia de rota indicou características de legibilidade e ruído, as quais foram consideradas na etapa de projeto. Posteriormente, um conjunto de mapas foi projetado com base nos aspectos da percepção de cores de indivíduos com deficiência na visão de cores e em princípios de comunicação cartográfica. O resultado do projeto foi constituído por uma única representação para a base cartográfica e duas cores para simbolizar automóvel, seta de direção de manobra e rota, totalizando oito diferentes mapas. A avaliação da preferência foi realizada junto a um grupo de 14 motoristas com deficiência na visão de cores...
Keywords: Cartografia; Sistema de Posicionamento Global - Avaliação; Automoveis; Daltonismo; Cartography